STUDI LITERATUR MENGENAI PERANCANGAN PROGRAM BIMBINGAN DAN KONSELING KOMPREHENSIF BIDANG LAYANAN PERENCANAAN INDIVIDUAL - Ayu Tri Yuningsih; Herdi Herdi (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2021)
The purpose of this article is to discuss the paradigm shift in the guidance and counseling approach, namely from a traditional, remedial, clinical, and counselor-centered approach to a developmental and preventive-oriented approach. The paradigm is comprehensive guidance and counseling. The purpose of a systemic comprehensive guidance and counseling program is to address the gap between the competency standards of students to be achieved and the abilities possessed by students in schools or in certain areas. One component of comprehensive guidance and counseling is individual planning services. Individual planning services are provided to all students and are intended to guide students in the development and implementation of personal, social, study, and career plans.